STUDI AB INITIO GRAFIT BATUBARA SEBAGAI MATERI PENYIMPAN HIDROGEN - Rahmat Gunawan; Melanie David; Hideaki Kasai; Muhammad A. Martoprawiro; Cynthia L. Radiman; Herman K. Dipojono (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2010)
Calculation of density functional theory (DFT) is carried out to investigate the adsorption of six molecules of H2 molecules on a graphite planar layer with a doping of alkali metal (Li, Na, and K). We reported that the DFT-GGA method, the presence of alkali metals on graphite, and H2-(GICs), have changed the interaction and the electronic system. We also reported that the ratio increased electron transfer from K to Na and Li. The calculation of the charge density shows that the increase in energy due to the transfer of electrical charge from GICs to six molecules of H2. This changes the electronic properties of graphite that are important in applications such as hydrogen storage.Keywords: Molecule Hydrogen, Graphite Intercalated Compounds, Density Functional Theory